The Ralstonia solanacearum Type III Effector RipAW Targets the Immune Receptor Complex to Suppress PAMP-Triggered Immunity - Sun, Zhi-Mao; Zhang, Qi; Feng, Yu-Xin; Zhang, Shuang-Xi; Bai, Bi-Xin; Ouyang, Xue; Xiao, Zhi-Liang; Meng, He; Wang, Xiao-Ting; He, Jun-Min; An, Yu-Yan; Zhang, Mei-Xiang (International journal of molecular sciences, 2023)
Bacterial wilt, caused by Ralstonia solanacearum, one of the most destructive phytopathogens, leads to significant annual crop yield losses. Type III effectors (T3Es) mainly contribute to the virulence of R. solanacearum, usually by targeting immune-related proteins. Here, we clarified the effect of a novel E3 ubiquitin ligase (NEL) T3E, RipAW, from R. solanacearum on pathogen-associated molecular pattern (PAMP)-triggered immunity (PTI) and further explored its action mechanism. In the susceptible host Arabidopsis thaliana, we monitored the expression of PTI marker genes, flg22-induced ROS burst, and callose deposition in RipAW- and RipAWC177A-transgenic plants. Our results demonstrated that RipAW suppressed host PTI in an NEL-dependent manner. By Split-Luciferase Complementation, Bimolecular Fluorescent Complimentary, and Co-Immunoprecipitation assays, we further showed that RipAW associated with three crucial components of the immune receptor complex, namely FLS2, XLG2, and BIK1. Furthermore, RipAW elevated the ubiquitination levels of FLS2, XLG2, and BIK1, accelerating their degradation via the 26S proteasome pathway. Additionally, co-expression of FLS2, XLG2, or BIK1 with RipAW partially but significantly restored the RipAW-suppressed ROS burst, confirming the involvement of the immune receptor complex in RipAW-regulated PTI. Overall, our results indicate that RipAW impairs host PTI by disrupting the immune receptor complex. Our findings provide new insights into the virulence mechanism of R. solanacearum.